'Vanishing cities': Can urban costs explain deindustrialization?1. (27th November 2014) - Goryunov, Maxim; Kokovin, Sergey
Abstract: Anas's impossibility theorem states that monopolistic competition or economies of scale alone are insufficient to explain growth of cities in response to growing population or decreasing trade costs (under constant urban costs); cities shrink. To enhance realism of assumptions, instead of Anas's normative approach, we study stable equilibria in the presence of another sector. Still, 'vanishing' remains robust! Ultimately, we argue that 'vanishing' mechanism looks realistic and can have an explanatory power: industries, free of externalities, should locate in small towns. Moreover, the comparative statics shows how such 'manufacturing' towns gradually decline, whereas other cities do not.